MEMBANGUN KARAKTER MELALUI PEMBELAJARAN SASTRA: PROBLEMATIKA PEMBINAAN KARAKTER - Ernawati, Yeni (Jurnal Ilmiah Bina Edukasi, 2018)
Character education is an ongoing process for transforming and building individual behavior into human beings who have good knowledge, attitude, and skills. Character building on the learner is needed because of the problematic in learning about dishonesty, indiscipline, and the violence done by the learner. Efforts to build individual characters can be implemented in learning materials and learning models. One effort to build the character of learners through literary learning. Literary works play an important role in the implementation of character education. The purpose of learning literature is learners are expected to develop honest behavior, discipline, responsibility, care, polite, environmentally friendly, mutual cooperation, cooperation, love peace, responsive and proactive by way of appreciating the literature to refine the character of learners. In the Kurikulum 2013, literary learning materials used as a means of building the character of learners are short story texts, fable, pantun (poem), and novel.